Genome-based reclassification of the family Stappiaceae and assessment of environmental forcing with the report of two novel taxa, Flexibacterium corallicola gen. nov., sp. nov., and Nesiotobacter zosterae sp. nov., isolated from coral and seagrass - Mi-Jeong Park; Jinnam Kim; Yun Jae Kim; Jihyun Yu; Hyein Jin; Seonok Woo; Young-Gun Zo; Kae Kyoung Kwon (PLoS ONE, 2025)
Two novel strains, MaLMAid0302T and SPO723T, isolated from coral and eelgrass, respectively, were distinguished from other Stappiaceae species based on phenotypic, biochemical, phylogenetic, and chemotaxonomic traits. Taxonomic challenges within the family Stappiaceae were addressed using a taxogenomic approach with iterative clustering, establishing an optimal average amino acid identity (AAI) threshold (71.92–72.88%) for genus delineation. This analysis led to major taxonomic revisions, including the establishment of new genera—Parapolycladidibacter, Astericibacter, Flexibacterium, Aliiroseibium, Laciiroseibium, Soliroseibium, Novilabrenzia, Litoriroseibium, and Algilabrenzia—as well as the reassignment of several species: Hongsoonwoonella albiluteola comb. nov., Parapolycladidibacter stylochi gen. nov., comb. nov., Astericibacter flavus gen. nov., comb. nov., Nesiotobacter exalbescens comb. nov., Aliiroseibium hamelinense gen. nov., comb. nov., Laciiroseibium aquae gen. nov., comb. nov., Soliroseibium sediminis gen. nov., comb. nov., Novilabrenzia suaedae gen. nov., comb. nov., Novilabrenzia litorale gen. nov., comb. nov., Litoriroseibium aestuarii gen. nov., comb. nov., Litoriroseibium limicola gen. nov., comb. nov., and Algilabrenzia polysiphoniae gen. nov., comb. nov. Given this extensive taxonomic reclassification of the family Stappiaceae, strain SPO723T (=KCCM 42324T = JCM 14066T) was classified as Nesiotobacter zosterae sp. nov., and Flexibacterium corallicola MaLMAid0302T (=KCTC 92348T = JCM 35474T) was designated as the type species of the newly established genus Flexibacterium. Close phylogenetic ties to Pseudovibrio, known for symbiosis, prompted analysis of niche-specific genetic compositions. Canonical Correspondence Analysis attributed 64% of genomic variation to phylogenetic forcing and 36% to environmental forcing. Functional adaptations included pectin and aromatic compound degradation in sediment strains, nitrogen reduction in flatworm strains, and sulfur metabolism in coral strains. The eelgrass strain exhibited dTDP-L-rhamnose synthesis, potentially aiding biofilm formation for adhesion in dynamic environments. These findings emphasize the roles of both environmental and phylogenetic forcing in shaping genomic diversity and highlight the ecological importance of the family Stappiaceae in marine habitat-associated niches.